2018
DOI: 10.1093/cid/ciy141
|View full text |Cite
|
Sign up to set email alerts
|

A Registry for Patients With Asplenia/Hyposplenism Reduces the Risk of Infections With Encapsulated Organisms

Abstract: Systematic, long-term approaches to post-splenectomy care can significantly reduce the risk of infection with encapsulated organisms among individuals with asplenia/hyposplenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…The incidence of IMD is highest among children <1 year and adolescents/young adults [148]. In addition to age, there are other populations considered at high risk of IMD, including individuals with functional or anatomic asplenia, complement deficiency and human immunodeficiency virus (HIV) [12, [149][150][151]. Indeed, individuals with complement deficiency and HIV have an approximately 1000-fold and 10-fold increased risk of IMD, respectively [82,[152][153][154].…”
Section: Imd In High-risk Groupsmentioning
confidence: 99%
“…The incidence of IMD is highest among children <1 year and adolescents/young adults [148]. In addition to age, there are other populations considered at high risk of IMD, including individuals with functional or anatomic asplenia, complement deficiency and human immunodeficiency virus (HIV) [12, [149][150][151]. Indeed, individuals with complement deficiency and HIV have an approximately 1000-fold and 10-fold increased risk of IMD, respectively [82,[152][153][154].…”
Section: Imd In High-risk Groupsmentioning
confidence: 99%
“…They also reported reduced incidences of infections among this cohort [47]. In another retrospective cohort study, Arnott A. et al concluded that systemic, long-term approaches can significantly minimize the risk of infection with encapsulated pathogens among splenectomized individuals [48]. According to Premawardena C et al, major benefits of the registry were not related to the knowledge but in the delivery of the recommended vaccines and the use of a medical alert card [49].…”
Section: Benefits Of Having a Spleen Registrymentioning
confidence: 77%
“…We also still have limited data on the proportion of patients with asplenia or hyposplenism who are not registered in Victoria, Tasmania and Queensland. Vaccine uptake rates appear higher among registered cohorts 11 compared to non‐registered cohorts, 12 suggesting a mechanism for lower rates of preventable infections in those on the spleen registry 14 …”
Section: Discussionmentioning
confidence: 99%
“…Where vaccination was known, 57% were fully vaccinated and 43% were not. A study in Victoria suggested that registration is associated with a reduction in vaccine‐preventable disease rates of 69% 14 . The costs of treating a case of OPSI remains highly variable, with cases notified to Spleen Australia costing up to $280,000 (in 2014).…”
mentioning
confidence: 99%